A importância da felicidade no ambiente de trabalho: estudo de caso na cooperativa de crédito de livre admissão de associados – SICOOB e COCREDI - Galle, Cândida Raquel (Universidade do Vale do Rio dos Sinos, 2017)
This work aims to contribute to the studies aimed at the feeling of belonging, through an analysis of happiness in the organizational context of the Sicoob Ecocredi Cooperative, presenting the reasons that bring happiness and those that make happiness to cooperative employees. In this context, this research sought to understand the variables that make up the scope of happiness in the work environment, to identify which ones facilitates and which ones hinders happiness within the cooperative. For this, the approaches on happiness, gross internal happiness, concepts of happiness and their variables were used as theoretical basis. For the data collection, the case study was carried out at the Credit Union of Free Admission of Associates - Sicoob Ecocredi, which operates in the financial branch, with the head office in the city of Três Coroas / RS. The contributors answered questionnaires that contributed to the analysis and interpretation of data in a quantitative way. As main results, the relationships with staff, remuneration, recognition and valuation, environment and happiness are identified; factors that contribute to a happy environment. It is understood that cooperative employees are happy in their work environment.
Keywords: Ambiente; Cooperativa; Felicidade; Environment; Cooperative; Happiness